2015
DOI: 10.1063/1.4936331
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrical activation in In-implanted Ge by C co-doping

Abstract: At high dopant concentrations in Ge, electrically activating all implanted dopants is a major obstacle in the fulfillment of high-performance Ge-channel complementary metal oxide semiconductor devices. In this letter, we demonstrate a significant increase in the electrically-active dopant fraction in In-implanted Ge by co-doping with the isovalent element C. Electrical measurements have been correlated with x-ray absorption spectroscopy and transmission electron microscopy results in addition to density functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…This is responsible for the relatively low In electrically active fraction (40.2%), given that In metal precipitation was not found in the sample. C-In pair formation as well as its similar effects on In solid solubility and electrical activation enhancement were observed in both C + In co-doped Si [3,[11][12][13] and Ge, [14][15][16] consistent with our results here with Si 0.35 Ge 0.65 . At the highest In concentration of 0.6 at%, In metal precipitation was found in both the In-implanted (Figure 2(a)) and C + In co-implanted (Figure 2(b)) samples.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…This is responsible for the relatively low In electrically active fraction (40.2%), given that In metal precipitation was not found in the sample. C-In pair formation as well as its similar effects on In solid solubility and electrical activation enhancement were observed in both C + In co-doped Si [3,[11][12][13] and Ge, [14][15][16] consistent with our results here with Si 0.35 Ge 0.65 . At the highest In concentration of 0.6 at%, In metal precipitation was found in both the In-implanted (Figure 2(a)) and C + In co-implanted (Figure 2(b)) samples.…”
supporting
confidence: 91%
“…Co-doping C with In is one of the most promising approaches to meet such a requirement. It has been reported that in both Si [3,[11][12][13] and Ge, [14][15][16] enhancement of In electrical activation was realized by C co-doping. Above-equilibrium solid solubility was attained in both substrates as a consequence of C-In pair formation that suppressed In precipitation.…”
mentioning
confidence: 99%
“…Some advanced methods such as GW [25] and hybrid functional [26] can yield correct band gap but require huge calculation cost which are hard to calculate heterojunctions involving around hundred atoms or more. Next, the calculations of semiconductor with impurities [27] also increase the calculation cost, especially when the concentration of one species is very small, because one needs to compute systems with a large number of host atoms to accommodate the impurities and to take configuration average over many calculations to obtain a more reliable physical result. Thirdly, transport property is crucial for heterojunction and related devices.…”
Section: Introductionmentioning
confidence: 99%
“…Further increasing the atomic concentration only leads to the formation of larger In particles with a cuboctahedron shape. Finally, it is important to note that even for the highest implantation fluence no In related nanoparticles were observed in the In + C doped system [3,4].…”
mentioning
confidence: 99%